Search for community : from liberalism to dhamma - Palshikar, Suhas (Occasional paper (University of Poona. Dept. of Politics and Public Administration) ;, 1994)
Political thoughts of Bhimrao Ramji Ambedkar, 1892-1956, Indian statesman.